Aspects of legal and ethical liability in international trade with B2B customised products: Industrial component sector experience - Vít Chlebovský (Trends Economics and Management, 2018)
Purpose of the article: There has been a growing demand for customised solution offers prepared by companies on both B2B and B2C markets. Strong focus on product customisation generates legal and ethical business aspects, especially in the international trade. The purpose of this article is company behaviour changes mapping and trend identification specifically in international trade within the industrial component sector based on performed qualitative research. Methodology/methods: Qualitative research in the form of research case studies was used. There were five companies selected representing a variety of industrial component suppliers, both producers and trade companies in different size categories located in several European countries. The research questions were formulated and research results and respective limitations were discussed. Scientific aim: The scientific aim consists in observing and describing the current situation and trends in international trade within the industrial component sector with a high involvement of the product customisation. An important aspect also includes a multidisciplinary approach of the article covering marketing, trade and legal business issues. Findings: The research results show an increasing importance of focus on offering product individualisation to customers as a key factor influencing their sustainable competitiveness. Companies also see an increased importance of related process optimisation, as well as streamlining customer communication. Conclusions: Based on the presented five case studies, it is possibly to identify a trend of an increased demand for closer cooperation of the component suppliers with their customers independent of the country of location. Customers are also asking for supplier's full responsibility for the solution delivered. On the other hand, companies are not yet ready to provide such services in an efficient way within the current structure of their distribution channels. In order to confirm those qualitative research results, there should be additional quantitative research prepared and performed mapping a broader range of companies in wider industrial sectors to get a better picture of both customer demands and company capabilities.
Keywords: K12; L10; M10; M31; 650; customer solutions; relationship marketing; product customization; legal liability; international trade; market orientation